Imaging the uptake of deuterated methionine in Drosophila with stimulated Raman scattering - Spratt, Spencer J.; Mizuguchi, Takaha; Akaboshi, Hikaru; Kosakamoto, Hina; Okada, Rina; Obata, Fumiaki; Ozeki, Yasuyuki (Frontiers in Chemistry, 2023)
Visualizing small individual biomolecules at subcellular resolution in live cells and tissue can provide valuable insights into metabolic activity in heterogeneous cells, but is challenging. Here, we used stimulated Raman scattering (SRS) microscopy to image deuterated methionine (d-Met) incorporated into Drosophila tissues in vivo. Our results demonstrate that SRS can detect a range of previously uncharacterized cell-to-cell differences in d-Met distribution within a tissue at the subcellular level. These results demonstrate the potential of SRS microscopy for metabolic imaging of less abundant but important amino acids such as methionine in tissue.